2017
DOI: 10.1088/1361-6501/aa940a
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new densimeter for the combined investigation of dew-point densities and sorption phenomena of fluid mixtures

Abstract: For the determination of dew-point densities and pressures of fluid mixtures, a new densimeter has been developed. The new apparatus is based on the well-established two-sinker density measurement principle with the additional capability of quantifying sorption effects. In the vicinity of the dew line, such effects cause a change in composition of the gas mixture under study, which can significantly distort accurate density measurements. The new experimental technique enables the accurate measurement of dew-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Richter and Kleinrahm have shown that these sorption effects can lead to errors in gravimetrically measured vapor densities of about 0.1% . The results of the present study will support our current work utilizing two- and four-sinker densimeters and will also lead to application in density determination with single-sinker densimeters, i.e., gravimetric sorption analyzers.…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…Richter and Kleinrahm have shown that these sorption effects can lead to errors in gravimetrically measured vapor densities of about 0.1% . The results of the present study will support our current work utilizing two- and four-sinker densimeters and will also lead to application in density determination with single-sinker densimeters, i.e., gravimetric sorption analyzers.…”
Section: Introductionsupporting
confidence: 81%
“…In an earlier manufacturing step, the sinker was sandblasted with average particle sizes of 125 μm and plasma polished to remove about 2 μm. Later, it was galvanically gold-plated, which usually results in a layer thickness of several μm . A photograph of the sinker is shown in Figure .…”
Section: Simulation Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Implementing a pressure transducer with higher accuracy at low pressures and then carrying out a comprehensive force transmission error analysis could be a possible solution. Alternatively, adapting the two-sinker or four-sinker , measurement techniques that incorporate a magnetic-suspension balance and inherently enable lower measurement uncertainties at pressures below 1.0 MPa could also achieve such a target.…”
Section: Discussionmentioning
confidence: 99%